Disseminated melioidosis in a young adult with undiagnosed diabetes mellitus: A case report (Indian Journal of Case Reports, 2025)
Melioidosis, caused by Burkholderia pseudomallei, is a potentially fatal infection endemic to Southeast Asia and Northern Australia. We present the case of disseminated melioidosis in a 27-year-old fisherman from South India with previously undiagnosed diabetes mellitus. He presented with prolonged low-grade fever, encephalopathy, and hyperosmolar hyperglycemic state. Blood cultures identified B. pseudomallei, and imaging revealed multiple hepatic abscesses, pulmonary nodules, splenic infarction, and renal involvement. Intensive care management included meropenem therapy, insulin infusion, and mechanical ventilation. The patient experienced secondary infections and complications such as pressure ulcers and cavitating lung lesions. Following a prolonged intensive care unit stay and antibiotic therapy, he recovered and was discharged in stable condition. This case emphasizes the need for heightened clinical suspicion of melioidosis in febrile patients from endemic regions, even in the absence of overt risk factors. Early microbiological diagnosis and targeted treatment are key to reducing morbidity and mortality in disseminated melioidosis.